Carvedilol increases seizure resistance in a mouse model of SCN8A-derived epilepsy - Wong, Jennifer C.; Escayg, Andrew (Frontiers in Pharmacology, 2024)
Patients with mutations that alter the function of the sodium channel SCN8A present with a range of clinical features, including mild to severe seizures, developmental delay, intellectual disability, autism, feeding dysfunction, motor impairment, and hypotonia. In an effort to identify compounds that could be potentially beneficial in SCN8A-associated epilepsy, Atkin et al. conducted an in vitro screen which resulted in the identification of 90 compounds that effectively reduced sodium influx into the cells expressing the human SCN8A R1872Q mutation. The top compounds that emerged from this screen included amitriptyline, carvedilol, and nilvadipine. In the current study, we evaluated the ability of these three compounds to increase resistance to 6 Hz or pentylenetetrazole (PTZ)-induced seizures in wild-type CF1 mice and in a mouse line expressing the human SCN8A R1620L mutation. We also evaluated the effects of fenfluramine administration, which was recently associated with a 60-90% decrease in seizure frequency in three patients with SCN8A-associated epilepsy. While amitriptyline, carvedilol, and fenfluramine provided robust protection against induced seizures in CF1 mice, only carvedilol was able to significantly increase resistance to 6 Hz-and pentylenetetrazole-induced seizures in RL/+ mutants. These results provide support for further evaluation of carvedilol as a potential treatment for patients with SCN8A mutations.